Improving Cooling Capacity of Condensation-Free Radiant Cooling for Low-Emissivity Chilled Ceiling via Adaptive Double-Skin Infrared Membranes - Ke Du; Ke Du; Huijun Wu; Huijun Wu; Yanling Guo; Yanling Guo; Gongsheng Huang; Xinhua Xu; Yanchen Liu; Yanchen Liu (Frontiers in Thermal Engineering)
Radiant cooling has well been acknowledged as energy efficient and thermal comfortable technology compared to conventional convective cooling. However, the radiant cooling exists two serious problems (viz., insufficient cooling capacity and high condensation risk) especially in hot and humid climate zones. By adding double-skin infrared transparent membranes (DIMs) onto radiant cooling panel, the air-contact surface can be separated from the cooling source surface, which makes it possible to use a low-temperature cooling source while maintaining air-contact surface higher than dew point temperature. The DIMs are transparent to radiant heat transfer which yields great cooling capacity while chilled ceiling has high emissivity (e.g., above 0.9). However, for metal chilled ceilings having low emissivity, radiant heat from cooling load to chilled ceiling would be reduced through DIMs, which results in insufficient cooling capacity. In this paper, a type of adaptive double-skin infrared membranes (a-DIMs) consisting a high-emissivity membrane and a high transparent membrane is proposed to improve cooling capacity of conventional metal chilled ceilings. The high-emissivity membrane serves as radiant cooling surface instead of low-emissivity chilled ceiling so as to improve radiant heat flux, while the high transparent membrane permits great radiant heat from cooling load to chilled ceiling. A combined heat transfer analysis based on semi-transparent surface radiation and natural convection were carried out to predict cooling capacity of condensation-free radiant cooling. The results indicate that the cooling capacity could be up to 101.9W/㎡ by adding a-DIMs consisting of a high-emissivity membrane of 0.96 and a high transparent membrane of 0.87, which is improved by 2 times compared to conventional metal chilled ceiling with low emissivity of 0.2. Moreover, the cooling capacity by adding a-DIMs is further improved by 25% compared to that by using both infrared transparent DIMs presented in our previous work. The results also indicate that the cooling capacity could be improved by above 2 times compared to conventional low-emissivity metal chilled ceiling by using the radiant cooling with a-DIMs for various humidity. It will be of great guidance for high-performance radiant cooling design without condensation and improved cooling capacity for low-emissivity metal chilled ceiling.